Functional and molecular studies in primary carnitine deficiency. Issue 12 (14th September 2017) - Frigeni, Marta; Balakrishnan, Bijina; Yin, Xue; Calderon, Fernanda R.O.; Mao, Rong; Pasquali, Marzia; Longo, Nicola
Abstract: Primary carnitine deficiency is caused by a defect in the OCTN2 carnitine transporter encoded by the SLC22A5 gene. It can cause hypoketotic hypoglycemia or cardiomyopathy in children, and sudden death in children and adults. Fibroblasts from affected patients have reduced carnitine transport. We evaluated carnitine transport in fibroblasts from 358 subjects referred for possible carnitine deficiency. Carnitine transport was reduced to 20% or less of normal in fibroblasts of 140 out of 358 subjects. Sequencing of the 10 exons and flanking regions of the SLC22A5 gene in 95 out of 140 subjects identified causative variants in 84% of the alleles. The missense variants identified in our patients and others previously reported ( n = 92) were expressed in CHO cells. Carnitine transport was impaired by 73 out of 92 variants expressed. Prediction algorithms (Polyphen‐2, SIFT) correctly predicted the functional effects of expressed variants in about 80% of cases. These results indicate that mutations in the coding region of the SLC22A5 gene cannot be identified in about 16% of the alleles causing primary carnitine deficiency. Prediction algorithms failed to determine the functional effects of amino acid substitutions in this transmembrane protein in about 20% of cases. Therefore, functional studies in fibroblasts remain the best strategy to confirm or exclude a diagnosis of primary carnitine deficiency. Abstract : Primary carnitine deficiency can cause hypoketotic hypoglycemia, cardiomyopathy, and sudden death. It is caused by a defect in the OCTN2 carnitine transporter encoded by the SLC22A5 gene. DNA sequencing of the coding region failed to identify about 16% of the alleles causing primary carnitine deficiency (as determined by functional studies in fibroblasts) and common prediction algorithms incorrectly determined the functional effects of amino acid substitutions in about 20% of cases.